Serum Lactate Dehydrogenase as a Prognostic Marker of Childhood Acute Lymphoblastic Leukemia (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jul;17(2):169-73.The abstract of this article is available on the PubMed website